Analysis Strukturalism of the Novel Dream Launch Project by Renita Nozaria : Robert Stanton’s Theory - Hidayati, Nuril Hidayati (Institut Agama Islam Tarbiyatut Tholabah, 2024)
Dream Launch Project tells the story of Terry, a songwriter and producer who lost his zest for life after being diagnosed with Tinnitus and the possibility of total hearing loss for life. Terry lost the only thing he had. In this novel, there are several characters and Tertius Senandika as the main character. The purpose of this study is to analyze the structuralism, namely, character, plot, and conflict in Renita Nozaria's Dream Launch Project Novel. The method used is descriptive qualitative method with literary structural analysis approach. The author using Robert Stanton's theory of analyzing instrinsic elements (character, plot and conflict). The Conclutions of this study are 1) The characterization of the main character Tertius Senandika is the main character as a protagonist male and persistent in completing what has been entrusted to him. He has a character that does not give up easily, an expert in music, dexterous but a lover of solitude, Tsundere and loyal. 2) The conflicts studied in the novel Dream Launch Project are internal conflicts and external conflicts. 3) The plot goes back and forth because the story in the novel is densely packed with flashbacks from the introduction of the characters, Jeno, Nana, and Injun.